Biochemical and physiological differences between resistant and susceptible tomato cultivars infected by Ralstonia solanacearum Smith - SHOU Sen-yan; FENG Zhuang-zhi; YIN Yi-ping; TAN Yun; MIAO Li-xlang (浙江大学学报. 农业与生命科学版)
To study the physiological basis of tomato breeding for resistant to bacterial wilt, we inoculated the resistant and susceptible tomato cultivars with the pathogen bacterium to reveal the dynamic changes in the activities of four enzymes in plants of different cultivars in relation to their resistance. The results showed that the phenylanine ammonia lyase (PAL) activity of ‘T51A’, a resistant cultivar, was higher than that of the control (CK), while for ‘T9230’, a susceptible one, the activity was at about the similar level as the control (CK) following their infection by Ralstonia solanacearum. The resistant cultivar exhibited higher activity of superoxide dismutase (SOD) than the control (CK), with the peak value increased by 16.12%. But the susceptible cultivar was inferior to the CK, with the peak value decreased by 25.14%. The activity of peroxidase (POD) and polyphenoloxidase (PPO) did not differ significantly between resistant and susceptible cultivar. The capacity of the resistant cultivar in inhibiting chlorophyll disintegration and maintaining higher carotenoid content was significantly stronger than that of the susceptible cultivar.